The formal construction of video and wall technology inside the TV studio (Journal of the College of Basic Education, 2024)
This research deals with modern digital methods and mechanisms within the television studio, as well as the development and adaptation of the program presenter’s performance with this development of digital technologies and their penetration into television work. It has become necessary for television program makers and program presenters to be fully aware of these technologies, if the research deals with how to build The formal elements of television programs attract the recipient’s attention to events and news. The researcher divided the methodological framework into (the research problem, which ended with the question: What are the methods and mechanisms of the formal construction of video wall technology within the television studio? And then the importance of the research, the goal of the research, the limits of the research, and determining The most important terms. The theoretical framework is divided into two sections, the first of which was titled (Tools of the program presenter inside the studio), In this section, it dealt with the most important specifications that must be met by a program presenter and how to present the news bulletin in an interesting and attractive way when presented to the recipient. The second section was (the performance of the program presenter with video wall technology for television), as it dealt with change and adaptation of the program presenter and development. His abilities with digital technologies inside the studio. As for the research procedures, they were (research methodology, research population, research sample, research tool, validity of the tool, and this chapter concludes with the unit of analysis). Then (sample analysis), where the researcher analyzed a number of news bulletins broadcast by Al Jazeera satellite channel, and then the researcher reached the results: The video wall is of great importance in showing the facts and their credibility when presenting the news It has become necessary for the program presenter to develop his abilities to be consistent with the entry of the video wall into the studio. The cameras inside the studio now roam freely with the presenter’s movement and move to show events and images on the video wall screens. News bulletins and political reports became more attractive and popular with viewers after the video wall entered the studio. When the video wall enters the studio, the presenter must control what will be shown to the viewer. After entering the video wall, the presenter became more free to move around, interpret and give opinions when publishing news and reports, using what was shown on the video wall screens inside the studio.Then the researcher concluded his research with the sources and a summary in English.